2016
DOI: 10.3238/arztebl.2016.0423
|View full text |Cite
|
Sign up to set email alerts
|

Improving Treatment Adherence in Heart Failure

Abstract: Many effective interventions are available that can lead to sustained improvement in patient adherence and in clinical endpoints. Longterm success depends on patients' assuming responsibility for their own health and can be achieved with the aid of coordinated measures such as patient education and regular follow-up contacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 90 publications
0
46
0
2
Order By: Relevance
“…Heart failure (HF) is a syndrome characterized by frequent hospitalization, reducing quality of life, even causing death . To get a better chance to survive, besides systematic managements for patients with HF established, the various lifestyle factors play vital roles …”
Section: Introductionmentioning
confidence: 99%
“…Heart failure (HF) is a syndrome characterized by frequent hospitalization, reducing quality of life, even causing death . To get a better chance to survive, besides systematic managements for patients with HF established, the various lifestyle factors play vital roles …”
Section: Introductionmentioning
confidence: 99%
“…Drug therapy is one of the key parts of treating HF. Consequently, non-adherence to treatment directly affects the clinical outcomes and increases the risk of hospital- ization and death (11) . A systematic review that assessed the efficacy of interventions in patients with HF showed the improvement of at least one recommendation, whether adherence to treatment or a shift in lifestyle, reduce the risk of mortality by 2% and reduce the likelihood of hospitalization by 10% (12) .…”
Section: Discussionmentioning
confidence: 99%
“…В метаанализе [11] (2016) по данным 55 РКИ проведена оценка множества различных вмешательств по влиянию на приверженность 15016 пациентов с ХСН на стационарном и амбулаторном этапе лечения, включая 24 исследования по повышению приверженности к фармакотерапии и 42 исследования по повышению приверженности к модификации образа жизни. Вмешательства включали различные формы обучения пациентов по заболеванию, фармакотерапии и модификации образа жизни, визиты или телефонную поддержку медсестрой на дому, самоконтроль состояния, телемониторинг витальных показателей и приема ЛП, врачебный контроль, междисциплинарное наблюдение.…”
Section: приверженность пациентов с хснunclassified